High performance polymers - Cooper, Jan, editor (New York : NY Research Press, 2015)
This is a comprehensive book based on the chemistry as well as applications of high performance polymers. The properties of polyimides and heterocyclic polymers are well-known and they are utilized for long period temperature endurance ranging from 250 - 350'C. This book discusses synthesis, techniques, physicochemical properties, processing and applications of such polymers in advanced technologies. This book compiles original researches conducted by experts and covers all the disciplines related to this field and provides a comprehensive overview to the subject.